First measurement of [lambda] c baryon production in Au+Au collisions at √sNN=200 GeV - Adam, Jaroslav; Deppner, Ingo Martin; Weidenkaff, Philipp (Physical review letters, 2020)
We report on the first measurement of the charmed baryon Λ±c production at midrapidity (|y|<1) in Au+Au collisions at √sNN=200 GeV collected by the STAR experiment at the Relativistic Heavy Ion Collider. The Λc/D0 [denoting (Λ+c+Λ−c)/(D0+¯D0)] yield ratio is measured to be 1.08±0.16 (stat)±0.26 (sys) in the 0%-20% most central Au+Au collisions for the transverse momentum (pT) range 3<pT<6 GeV/c. This is significantly larger than the pythia model calculations for p+p collisions. The measured Λc/D0 ratio, as a function of pT and collision centrality, is comparable to the baryon-to-meson ratios for light and strange hadrons in Au+Au collisions. Model calculations including coalescence hadronization for charmed baryon and meson formation reproduce the features of our measured Λc/D0 ratio.